Bridging the gap: Crypto users’ sense-making of a historical market crisis - Annika Aebli; Fabienne Silberstein-Bamford (Journal of Digital Social Research)
The conflict between cryptocurrencies’ ideological promises and their practical reality has recently become a considerable topic of scholarly discussion. It has been framed in terms of the so-called ‘promissory gap’ of cryptocurrencies – a gap that is founded in the contrast between the promises of a ‘trust-free’ system and actual reality. Yet, while crypto’s notion of ‘trust-free’ money has been heavily questioned, there is little research on how users seek to overcome cryptocurrencies’ promissory gap. Contrary to the promises of being ‘trust-free’ by design, this paper demonstrates that struggles for trust and control represent a focal point of the community interactions surrounding crypto. By drawing upon Dervin’s sense-making methodology to conduct interviews with 28 crypto investors, this study examines how social actors attempt to construct ‘bridges’ over a ‘gap-filled’ reality related to the moment of a historical crisis in crypto. The results reveal crypto’s intricate social embeddedness: whilst unequal power dynamics, distrust, and conflicting interests represent primary elements of users’ struggles in the crypto space, users attempt to restore a sense of control by recalling personal motivations and connecting with like-minded people. The paper provides insights into crypto users’ strategies to construct meaning in a highly uncertain environment and contributes to the discussion of crypto as a socially structured phenomenon.